(untitled) (Journal of Pharmaceutical Negative Results, 2022)
In Things Fall Apart the readers get to know about a few Ibo societies of both the precolonial and colonial times. The protagonist of the novel Okonkwo is shown to have different viewpoints regarding the society of his fatherland, Umuofia of the precolonial and colonial times. He respected and lived by the rules of the society in the precolonial times but after the arrival of the colonizers, there could be seen emergence of different viewpoints and opinions between Okonkwo and the larger society. The society changed a lot as a result of the arrival of the colonizers who brought rules and regulations that were not always beneficial to the society. As Okonkwo found it hard to understand the changing nature of the society and also at times because of holding a different viewpoint than the other tribesmen regarding various ideas and issues like revenge, violence etc. along with regarding the colonizers, he had to suffer which ultimately led to his end.